Current aspects of Quality Control and Standardization of Eleutherococcus senticosus Medicines - V. A. Kurkin; T. K. Ryazanova (Разработка и регистрация лекарственных средств)
Introduction. Nowadays, herbal medicines are becoming more and more popular. In this regard, herbal medicinal preparations based on rhizomes and roots of Eleutherococcus senticosus (Rupr. & Maxim.) Maxim., syn. Acanthopanax senticosus (Rupr. & Maxim.) Harms, are of particular interest. Its have an adaptogenic, immunomodulatory effects mainly due to the presence of phenyl propane compounds: eleutherosides B, D, E, E1. The current pharmacopeial monographs FS.2.5.0053.15 "Eleutherococcus senticosus rhizomes and roots" and FS.3.4.0009.18 "Eleutherococcus senticosus rhizomes and roots liquid extract" in The State Pharmacopoeia of the Russian Federation XIV Edition, in our opinion, does not allow to fully objectively and uniformly assess the quality of raw materials and preparations.Aim. The aim is substantiation of new approaches to quality control of raw materials and preparations of Eleutherococcus senticosus, consisting in changing the conditions of sample preparation and analysis of active biological compounds in comparison with pharmacopoeial methods.Materials and methods. Samples of the medicinal preparation "Eleutherococcus extract liquid" of a domestic manufacturer (5 lots) and experimental preparation "Eleutherococcus syrup". When performing high performance liquid chromatography (HPLC) analysis, a reference sample of syringin was used that met the requirements of pharmacopeial monograph VFS 42-2088-92. Methods of UV-spectroscopy and HPLC were used to determine the quantity of biologically active substances.Results and discussion. As a result of the research, other methodological and methodological approaches have been developed to determine the content of the total of phenylpropanoids in terms of eleutheroside B (syringin) by direct UV-spectrophotometry using a standard sample of syringin or the value of its specific absorbance. New conditions for HPLC analysis of eleutheroside B (syringin) in preparations of Eleutherococcus senticosus have been selected.Conclusion. As a result of the phytochemical study, a spectrophotometric method was developed for the determination of the total of phenylpropanoids in terms of syringin and an HPLC method for the determination of eleutheroside B (syringin) using an external standard after preliminary purification of the total extracts by filtration through a layer of aluminum oxide.